Impact of Technology in Improving the Quality of Education and Human Resource Development - Silvy Sondari Gadzali (Indo-MathEdu Intellectuals Journal, 2023)
Education and human resource development have an important role in the progress of a country. In the era of globalisation and the information technology revolution, rapid changes in technology have created a variety of new opportunities and challenges in the education and human resource development sectors. The purpose of this study is to analyse the impact of technology in improving the quality of education and human resource development. This research uses a qualitative methodology in the form of a literature review, which implies that the research will examine and explain data by utilising information and textual content from various sources. The study results show that the influence of technology in improving the quality of education and human resource development has considerable weight. Changes in learning methods have sparked various developments in the education domain, including distance learning, online learning platforms, and entertainment-oriented learning models that encourage learning to be more engaging and collaborative.